11. CASE REPORT: CUTANEOUS LEUKOCYTOCLASTIC VASCULITIS DUE TO ANTI-TUBERCULOSIS MEDICATIONS AT NATIONAL LUNG HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Introduction: Anti-tuberculosis drug-associated cutaneous adverse reactions are common in the treatment of tuberculosis. Cutaneous adverse reactions commonly encountered include: Morbilliform rash, exfoliative dermatitis, urticaria, psoriasiform drug eruption, lichenoid eruption, toxic epidermal necrolysis, Stevens-Johnson syndrome... However, cutaneous leukocytoclastic vasculitis (LCV) due to anti-tuberculosis medications is a rare adverse reaction.Objective: This article aims to report a case of cutaneous LCV due to anti-tuberculosis medications. The primary goals include contributing to scientific data, as well as sharing insights into the diagnostic and treatment processes.Case report: We describe a 70-year-old male diagnosed with pulmonary tuberculosis, treated with a regimen including rifampicin, isoniazid, pyrazinamide, and ethambutol. After 1 months of treatment, the patient developed multiple purpuric papules in the extremities. Histopathological results from skin biopsy were consistent with leukocytoclastic vasculitis. The skin lesions gradually resolved after discontinuation of tuberculosis medications and treatment with corticosteroids and antihistamines. Each tuberculosis medication was reintroduced every 4 days. Purpuric papules recurred when the patient rechallenged pyrazinamide at a dose of 500 mg and after that, rifampicin at a dose of 450 mg.Discussion: The discussion focuses on the epidemiology, the etiology and the treatment of LCV. In this case, we report about how we can diagnose LCV in this case by pathology and provocation test.Conclusion: This is a rare case of cutaneous leukocytoclastic vasculitis due to rifampicin and pyrazinamide.
Keywords: Cutaneous leukocytoclastic vasculitis; rifampicin; pyrazinamid; pulmonary tuberculosis.